370. Clinical Features and Outcomes of COVID-19 Infection Among Cancer Patients in Seattle, Washington. (31st December 2020) - Yoke, Leah H; Yoke, Leah H; Lee, Juhye; Krantz, Elizabeth M; Morris, Jessica; Marquis, Sara; Bhattacharyya, Pooja; So, Lisa; Riedo, Francis X; Simmons, Jason; Khaki, Ali R; Pergam, Steven A; et al.
Abstract: Background: High morbidity and mortality has been observed with COVID-19 infection; however, there are limited data on clinical characteristics including exposures, coinfections, and antimicrobial use among cancer patients. We aimed to better characterize clinical features and outcomes in this population. Methods: We conducted a retrospective chart review of consecutive patients at the Seattle Cancer Care Alliance diagnosed with SARS-CoV-2 infection by RT-PCR between February 28, 2020 and May 3, 2020. We obtained demographic and clinical data including coinfections, antimicrobial use and outcomes at 30 days after diagnosis. Results: Of 60 patients reviewed, the median age was 62 years (range 22–98) and 43% were male. 34 (57%) patients had solid tumors and 16 (27%) hematologic malignancies. Breast (12%), colorectal (8%) and non-Hodgkin lymphoma (8%) were the most prevalent cancers. 34 (57%) had ≥ 2 comorbidities. The majority of identified exposures were from long-term care facilities (LTCF) (27%) or household contacts (25%) (Fig 1). The most common symptoms at diagnosis were cough (72%), fevers/chills (57%), shortness of breath (38%), nasal congestion/rhinorrhea (35%), and diarrhea (30%). 18 (31%) patients were prescribed at least one course of antibiotics within 30 days of diagnosis; antibiotics were prescribed to 54% of hospitalized patients (Fig 2). 6 (10%) had a documented bacterial infection; of these, 3 were respiratory coinfections. No viral or fungal copathogens were reported. 26 (43%) patients were hospitalized, 9 (15%) admitted to intensive care, and one (2%) required mechanical ventilation. 12 (20%) died within 30 days of diagnosis (Fig 3); of these, 10 (83%) had ≥ 2 comorbidities and 8 (67%) had LTCF exposure. Conclusion: COVID-19 is associated with significant morbidity and mortality in cancer patients, particularly among older age groups with multiple comorbidities and those with LTCF exposure. More than half of cases appeared to acquire SARS-CoV-2 from LTCF or household exposures, indicating need for infection prevention and family/caregiver education. Despite few documented bacterial coinfections, antibiotic use within 30 days of diagnosis was common and likely empiric due to limited diagnostics in the era of COVID-19. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis) Alpana Waghmare, MD, Amazon (Grant/Research Support)Amazon (Employee, Shareholder)Ansun Biopharma (Scientific Research Study Investigator)Kyorin Pharmaceuticals (Advisor or Review Panel member)